Research in probation settings: experience and "field policy" - Lambelet, Daniel (Fieldwork experiences in criminology and security studies, 2023)
Our contribution represents an account of the complexity and challenges encountered by social work and social science researchers conducting a study in the field of probation. In order to highlight these issues, we share our experience of a field study conducted between 2018 and 2019 in three probation services in French- and Italian-speaking Switzerland. We describe the conditions of access to the field, the specific characteristics of our methodological apparatus, the construction of our corpus of data, as well as the communication of the results of the study. We demonstrate how a reflexive approach and a certain amount of methodological creativity enabled us to obtain and retain the sometimes fragile agreements that were granted to us by gatekeepers "under surveillance."